The relationship between ergonomic and employees' performance at Petronas Gas Berhad in Kerteh, Terengganu / Ratina Erna Abdul Aziz - Abdul Aziz, Ratina Erna (2015)
The objective of this research is to determine the relationship between ergonomic and employees' performance at the Petronas Gas Berhad in Kerteh, Terengganu. The study population consisted of 122 employees at the Petronas Gas Berhad. The ergonomic in the workplace give good results to see how it related to employees performance. The previous researcher also stated that ergonomic in the workplace give a good relationship to employees' performance as a result give the same answer. As the results given, ergonomic are the foundation to employees' performance.